Cost Accounting : An Asia Edition - William K. Carter (Cengage Learning, 2015)
Cost Accounting: An Asia Edition emphasizes the use of accounting information in planning and controlling a business and in supporting management decisions, including strategic decisions that position the firm to compete better. The book not only demonstrates the mechanics of alternative accounting systems and techniques for the needs of different companies, but also explains the logic behind different alternatives. The objective is to help the student learn to look at the business first and then to design an accounting system that can collect and generate the kind of information needed. It also illustrates and explains the cost concepts and objectives, cost accumulation, planning and control of costs, budgeting and standard costs, and analysis of cost and profit at the corporate or individual entity levels by using the most updated set of International Financial Reporting Standards (IFRS).